2022
DOI: 10.46918/bn.v5i1.1222
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sikap Belajar Mahasiswa Terhadap Pembelajaran Secara Online

Abstract: Penelitian ini bertujuan untuk mendeskripsikan sikap belajar mahasiswa terhadap Pembelajaran online pada Prodi Pendidikan Biologi Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Alauddin Makassar. Jenis penelitian ini adalah penelitian kualitatif. Instrumen penelitian berupa angket (skala Linkert). Responden penelitian berjumlah 30 mahasiswa sebagai populasi pada mahasiswa angkatan 2019 Program Studi Pendidikan Biologi UIN Alauddin Makassar dengan teknik pengambilan sampel purposive sampling. Hasil pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…Aside from that, students will respond quickly to everything communicated through online learning activities. These results are in line with the results of research conducted by Arif et al (2022), which revealed that Student attitudes remain consistent whether learning is done online or offline. Where students still have a positive attitude toward learning.…”
Section: Discussionsupporting
confidence: 91%
“…Aside from that, students will respond quickly to everything communicated through online learning activities. These results are in line with the results of research conducted by Arif et al (2022), which revealed that Student attitudes remain consistent whether learning is done online or offline. Where students still have a positive attitude toward learning.…”
Section: Discussionsupporting
confidence: 91%
“…Kesesuaian antara isi pembelajaran dengan tujuan pembelajaran sangat berperan penting dalam pengembangan media demi tercapainya kualitas pembelajaran yang maksimal (Angga et al, 2020;Astra et al, 2013;Rahmatika & Ratnasari, 2018). Tujuan pembelajaran yang jelas dapat menjadi sebuah pedoman dalam pembelajaran yang berlangsung (Arif & Yanawati, 2018).…”
Section: Pembahasanunclassified
“…Berdasarkan hasil tersebut dapat disimpulkan bahwa tujuan pembelajaran, startegi pembelajaran, materi pembelajaran, evaluasi yang sesuai sangat perlu untuk diperhatikan dalam mengembangkan sebuah video pembelajaran. Strategi pembelajaran adalah perpaduan dari rangkaian kegiatan, cara memberikan materi, serta waktu yang digunakan untuk mencapai tujuan pembelajaran yang telah direncanakan (Arif & Yanawati, 2018). Maka dari itu menguasai startegi dalam mengajar sangat penting dikarenakan karakteristik setiap siswa berbeda-beda dan jenis perilaku siswa beragam sehingga alangkah baiknya guru kaya akan strategi dalam mengajar.…”
Section: Pembahasanunclassified
“…A positive learning attitude can be developed by students and lecturers as educators must find ways for students' positive attitudes to appear in online lectures. One alternative for increasing positive attitudes in online learning is, (1) growing the need to get appreciation, appreciate the beauty, and so on; (2) connecting with experience; (3) providing the opportunity to obtain the best results; (4) using various teaching methods such as discussions, demonstrations, reading, group work and so on (Arif et al, 2022).…”
Section: Introductionmentioning
confidence: 99%